Peran Aktor Utama Dalam Menyampaikan Pesan Kepada Penonton Melalui Film Antara Kopi Dan Skripsi - Afridho Irawan; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This final project is compiled based on the author's experience during the production activities of making a film entitled "Between Coffee and Thesis". During the pre-production and shooting process, the author served as the main actor. The main actor's task is to play a role as a character or figure that matches the expectations of the story of a film. The main actor must be able to understand the character in depth, including the background, motivation, and emotions involved. In addition, the actor must also be able to adapt to different roles and understand the director's direction. This film production activity aims to improve the author's ability to communicate, increase relationships and be able to apply the knowledge learned during college so that they get a picture of the world of work later. During the film production activities, the author has observed and felt for himself how important the process is in playing a role in a film, especially as the main actor who needs maximum results so that it becomes one of the factors for the success of a film. Starting from character development, paying attention to acting skills to understanding what needs are needed so that the character is successfully played from all aspects. So in its application, good communication is needed between the actor and the team so that good cooperation is established. Interpersonal communication theory is the process of sending and receiving messages with the aim of getting feedback and reactions so that the message to be conveyed can influence behavior between two or more people. So that the role of the main actor has a very important essence in the production of a film.